Biomonitoring of pesticides, pharmaceuticals and illicit drugs in a freshwater invertebrate to estimate toxic or effect pressure. (August 2019) - Miller, Thomas H.; Ng, Keng Tiong; Bury, Samuel T.; Bury, Sophie E.; Bury, Nicolas R.; Barron, Leon P.
Abstract: Multiple classes of environmental contaminants have been found in aquatic environments, globally. Understanding internalised concentrations in the organism could further improve the risk assessment process. The present study is concerned with the determination of several contaminant classes (107 compounds) in Gammarus pulex collected from 15 sites covering 5 river catchments across Suffolk, UK. Quantitative method performance was acceptable for 67 compounds including pharmaceuticals, pesticides, illicit drugs and drugs of abuse. A total of 56 compounds were detectable and ranged from <LOQ to 45.3 ng g −1, with cocaine and lidocaine being the most frequently detected compounds present in all biota samples ( n = 66). For surface water, 50 compounds were detectable and ranged from <LOQ to 382.2 ng L −1 . Additionally, some pesticides currently not approved for use were detected, including fenuron that reached a maximum of 16.1 ng g −1 . The internal concentrations of pesticides were used to estimate toxic pressure which showed that for the measured pesticides toxic pressure was low ranging from logTU ≤−7 to ≤−2. This methodology was extended to pharmaceuticals and drugs of abuse in a novel approach that proposed the use of pharmacological data (human therapeutic plasma concentrations) to estimate the likelihood of an effect (or effect pressure) to occur based on the internal exposure of the organism. The quantified effect pressure ranged from logEU ≤−9 to ≤1 with haloperidol showing the largest likelihood for an effect. The approach showed that several pharmaceuticals have the potential to elicit effects but further investigation surrounding thresholds for effects would be required. This new approach presented showed potential to be used to improve risk assessment for pharmaceuticals in the environment. Graphical abstract: Unlabelled Image Highlights: A method is presented to quantify pesticides, pharmaceuticals and drugs of abuse. Cocaine was the most frequently determined compound found in 100% of samples. Several pesticides no longer approved for use in the EU were determined. Estimates of toxic pressure for detected pesticides was low. Effect pressure of drugs showed good potential to prioritise compounds of concern.